ART THERAPY METHOD AS A MEANS OF MANAGING EMOTIONS FOR JUNIOR HIGH SCHOOL STUDENTS AT BANDUNG - Widyastuti, Linda; Sukmana, Priscalina Dea; Hudaya, Salsa Bila; Ramadhan, Muhammad Azhar (International Research of Multidisciplinary Analysis, 2024)
In the psychological changes that occur in adolescence, one of them is socio-emotional changes, when they have high emotional tension. This creates the pressures for adolescents, such as the pressure of academic performance, the need to be popular, the desire to be accepted in an appropriate social group. The ability to be able managing the emotions for adolescents is related with habit of experiencing various problems that pressurize themselves such as stress, anxiety and depression. They should have the ability to manage adaptive of emotion. Some studies state that art therapy helps to explore one's feelings, reconcile emotional conflicts,, develop social skills, reduce anxiety, etc. Researchers conducted research using descriptive qualitative methods, with data collection using observation and interviews with 5 adolescent respondents aged 11-15 years in one of the junior high schools in Bandung City. Based on the results of the study, it was found that the five respondents were able to manage their emotions adaptively, but there were still respondents who did not understand much about the types of emotions and how to respond when others showed negative emotions. Art therapy groups were given and the results showed that there were respondents who felt suitable for art therapy done in groups, but there were also those who preferred to work alone because they felt more free to express themselves. There needs to be clear rules given before the activity and needs to be done on an ongoing basis so that art therapy groups can be felt the benefits